Efficacy of the Buzzy Device for Pain Management During Needle-related Procedures: A Systematic Review and Meta-Analysis. Issue 6 (June 2019) - Ballard, Ariane; Khadra, Christelle; Adler, Samara; Trottier, Evelyne D.; Le May, Sylvie
Abstract : Objective: This systematic review and meta-analysis examined the effectiveness of the Buzzy device combining cold and vibration for needle-related procedural pain in children. Materials and Methods: Databases search was conducted from inception to December 2017 to identify randomized controlled trials using the Buzzy device for pain management in children undergoing needle-related procedures. Selection of studies, data extraction, and assessment of risk of bias and quality of evidence were independently performed by 2 reviewers. Quantitative and qualitative analyses were conducted. Results: A total of 9 studies involving 1138 participants aged between 3 and 18 years old were included in the systematic review and 7 were suitable for meta-analysis. The meta-analysis compared the Buzzy device with a no-treatment comparator and the effect of the device was significant in reducing self-report procedural pain (standardized mean difference [SMD]: −1.11; 95% confidence interval [CI]: −1.52 to −0.70; P <0.0001), parent-reported procedural pain (SMD: −0.94; 95% CI: −1.62 to −0.27; P =0.006), observer-report procedural pain (SMD: −1.19; 95% CI: −1.90 to −0.47; P =0.001), observer-reported procedural anxiety (SMD −1.37; 95% CI: −1.77 to −0.96; P <0.00001), and parent-reported procedural anxiety (SMD −1.36; 95% CI: −2.11 to −0.61; P =0.0004). There was no significant difference for the success of the procedure at first attempt and the occurrence of adverse events. Discussion: The Buzzy device seems to be a promising intervention for procedural pain management in children. However, the comparative effect is uncertain due to the presence of significant heterogeneity and very low-quality evidence. There is a need to improve the methodological quality and rigor in the design of future trials to conclude to the efficacy of the Buzzy device. Abstract : Supplemental Digital Content is available in the text.